Degermed corn distiller’s grains with solubles (DGS) have feed value similar to traditional distiller’s grains - Loe, E.R.; Quinn, M.J.; Corrigan, M.E.; Depenbusch, Brandon E.; Drouillard, James S. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Rapid expansion of the fuel ethanol industry has greatly increased availability of distillery byproducts. Distiller’s grains with solubles (DGS) are the predominant byproduct of fermenting grains into fuel ethanol. During this process, starch is removed from the grain and the residual components of the grain are concentrated in the DGS. Improvements in the conversion of cereal grains to ethanol have been fueled by recent changes in the production process. Broin Companies (Sioux Falls, SD) have developed a technology that removes the germ before the fermentation process. The resulting byproduct contains more protein, less crude fat, and less phosphorus compared to traditional distiller’s grains. Feeding even modest levels of DGS can contribute to greater phosphorus excretion from feedlots, suggesting that strategies aimed at reducing phosphorus levels are well warranted. The objective of this study was to compare diets based on steam-flaked corn with and without DGS and to compare a highprotein, low-fat, low-phosphorus byproduct to more traditional distiller’s grains.
Keywords: Beef; Cattle; Distiller’s grains with solubles (DGS); Degermed corn